English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. -68
b. 4
c. -20
d. 52

2007-03-21 02:07:49 · 5 answers · asked by lana l 1 in Science & Mathematics Mathematics

5 answers

g(x) = 3x - 8
g(-4) = (3)(-4) - 8 = -12 - 8 = -20

g[g(-4)] = g(-20)

g(-20) = (3)(-20) - 8 = -60 - 8 = -68

2007-03-21 02:14:18 · answer #1 · answered by MamaMia © 7 · 1 0

Do it from the inside out.
g(-4) = 3(-4)-8 = -20
g(-20) = 3(-20) -8 = -68.

2007-03-21 02:17:43 · answer #2 · answered by steiner1745 7 · 1 0

g(-4) = 3 * (-4) - 8 = -12 - 8 = -20
g(g(-4))=g(-20)= 3 * (-20) - 8 = -68

2007-03-21 02:20:10 · answer #3 · answered by Anonymous · 1 0

Mama Mia is right -68

2007-03-21 02:18:08 · answer #4 · answered by theFo0t 3 · 1 0

g(-4)=3(-4)-8
=-12-8=-20
3(-20)-8=
-60-8=-68

The answer is a.

2007-03-21 02:32:23 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers